The Influence Of The Environment And Work Ethic In Improving Performance With Communication As A Moderator Variable In The Regional Financial And Revenue Management Agency Of Jambi Province - Ulfah Yasarah; Sry Rosita; Fitri Chairunnisa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study examines the influence of environment and work ethic in improving employee performance with communication as a moderating variable at BPKPD of Jambi Province. A quantitative method was applied in this study with a population of 167 civil servants and a sample of 118 respondents. Data were collected through questionnaires and analyzed using descriptive analysis and Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings show that the work environment and work ethic have a positive and significant effect on employee performance, while communication does not have a significant effect on employee performance. Furthermore, communication does not moderate the effect of the work environment on employee performance, but it significantly weakens the effect of work ethic on employee performance.